Relation of selenium status to neuro-regeneration after traumatic spinal cord injury - Heller, Raban; Seelig, Julian; Bock, Tobias; Haubruck, Patrick; Grützner, Paul Alfred; Schomburg, Lutz; Moghaddam-Alvandi, Arash; Biglari, Bahram (Journal of trace elements in medicine and biology, 2019)
Introduction - The trace element selenium (Se) is crucial for the biosynthesis of selenoproteins. Both neurodevelopment and the survival of neurons that are subject to stress depend on a regular selenoprotein biosynthesis and sufficient Se supply by selenoprotein P (SELENOP). - Hypothesis - Neuro-regeneration after traumatic spinal cord injury (TSCI) is related to the Se status. - Study design - Single-centre prospective observational study. - Patients and methods - Three groups of patients with comparable injuries were studied; vertebral fractures without neurological impairment (n = 10, group C), patients with TSCI showing no remission (n = 9, group G0), and patients with remission developing positive abbreviated injury score (AIS) conversion within 3 months (n = 10, group G1). Serum samples were available from different time points (upon admission, and after 4, 9 and 12 h, 1 and 3 days, 1 and 2 weeks, and 1, 2 and 3 months). Serum trace element concentrations were determined by total reflection X-ray fluorescence, SELENOP by ELISA, and further parameters by laboratory routine. - Results - Serum Se and SELENOP concentrations were higher on admission in the remission group (G1) as compared to G0. During the first week, both parameters remained constant in C and G0, whereas they declined significantly in the remission group. Similarly, the concentration changes between admission and 24 h were most pronounced in this group of recovering patients (G1). Binary logistic regression analysis including the delta of Se and SELENOP within the first 24 h indicated an AUC of 90.0% (CI: 67.4%-100.0%) with regards to predicting the outcome after TSCI. - Conclusion - A Se deficit might constitute a risk factor for poor outcome after TSCI. A dynamic decline of serum Se and SELENOP concentrations after admission may reflect ongoing repair processes that are associated with higher odds for a positive clinical outcome.